Sustainable solid waste management Measures in Tanzania: an exploratory descriptive case study among vendors at Majengo market in Dodoma City - Kepha Nyampundu; William J. S. Mwegoha; Walter C. Millanzi (BMC, 2020)
Abstract Background Solid waste management is both an urban and rural problem because every person is considered a producer of wastes. It has been noted to be a global universal issue, which affects every individual, families, communities and governments and thus, needs to be addressed through sustainable strategies. This study aimed at characterizing solid wastes; assessing the levels of awareness of vendors on the sustainable solid waste management measures; and identifying techniques used to handle solid waste generated at the Majengo market in Dodoma City, Tanzania. Methods The study adopted an exploratory descriptive case study, with a mixed research approaches with a minimum sample of 196 conviniently selected respondents. Semi-structured questionnaires developed by the researcher were the main data collection tools to characterize solid wastes, measure levels of awareness about sustainable solid waste management approaches (SWM) and identify solid waste handling techniques among vendors at the market. Quantitative and Qualitative data were analyzed by using the Statistical Product for Social Sciences version 23 and thematic analysis respectively. Results Findings showed that 55% of vendors were males. Majority of the sampled vendors (56%) were not aware of SWM. On the other hand, crops/food and animal product remains were reported to be the most generated solid wastes (94.4%) with the rate of > 2 tons/day equivalent to 72.4% of the overall solid waste generation at the market. SWM services were reported to be provided by City council (85.7%) with the main equipment/tool used to store solid wastes (SW) being containers without lids (88.3%). The dumpsite was the main site for SW disposal (80.1%). Nevertheless, 92.9% of the sampled vendors reported that SWM strategies were there at the market though not adhered to accordingly. Conclusion Vendors were not aware of sustainable solid waste management measures existing at the market. However, vendors' education levels and the duration of doing business at the market were related to their levels of awareness on SWM (p < 0.05). The SWM measures were found to exist at the market, however, they were not sustainable because it was reported that they were ineffectively and inefficiently used to control SW generation, collection, storage, and disposal. There is a need of regular awareness-raising activities about sustainable SWM measures among vendors. Moreover, city council and market authorities need to have sustainable and scheduled implementation, supervision, monitoring and evaluation of SWM measures to maintain the management of solid wastes at Majengo market premises.